Dosis de ruminaza en las características vegetativas y rendimiento del forraje de Canavalia ensiformis L. canavalia en Zungarococha, Perú - Zegarra Massari, Giuseppe Gianmarco (2024)
The use as a biofertilizer of by-product of the fields such as ruminaza must be managed to provide soil improvement for forage production. The title of this work is: “RUMINAZA DOSE IN THE VEGETATIVE CHARACTERISTICS AND FORAGE YIELD OF Canavalia ensiformis L. CANAVALIA IN ZUNGAROCOCHA, PERU” With a Complete Random Block Design (RCD), with four treatments and four repetitions, the treatments under study are T0 (control), T1 (10 t ruminaza/ha), T2 (30 t ruminaza/ha) and T3 (30 t ruminaza/ha). In the investigation, the following conclusions were reached: treatment T3 (30 t ruminaza/ha). It surpassed the other indicators of the research with a plant height of 93.8 centimeters, green matter of 2.43 kg/m2 and dry matter of 0.51 kg/m2, coverage of 94.25 percent, weight of leaves with 1.26 kg/m2, weight stem of 1.17 kg/m2 and a yield of 24,300 kg/ha., within 60 days of sowing.